Efektivitas Monopoli Akad Syariah (Monasy) Sebagai Media Pembelajaran Literasi Keuangan Syariah Bagi Mahasiswa - Hidayati, Athi’; Mahfudiyanto, Mahfudiyanto (MALIA: Journal of Islamic Banking and Finance, 2018)
This study aims to: developing Islamic monopoly contract learning media in muamalah fiqh courses. This study uses a research and development model with a procedure that is simplified into three stages according to the ADDIE model (Analysis, Design, Development or Production, Implementation, Delivery and Evaluation).Design (conversion of the functions of the general monopoly component to the Islamic monopoly contract and designing media designs before being made using Corel Draw X5), Development or Production (based on the design that has been made on paper, the researcher made a monopoly Islamic contract (monasy) learning media with Corel Draw X5 and validated the material test, media test). Effektivitas of monopoly Islamic contract (monasy) learning media according to material experts and media experts is "feasible" to be used as Islamic financial literacy learning media.